2000
DOI: 10.1080/026404100365153
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental factors on rugby football injuries

Abstract: The aim of this study was to establish the influence of weather and pitch conditions on the frequency and nature of rugby injuries. Observers at 26 senior rugby clubs in the Borders District of the Scottish Rugby Union reported all injuries to 1169 (96%) registered players at Saturday home and away matches during the 1993-94 season (August 1993 to April 1994). Weather and pitch conditions at 112 grounds were recorded on 605 occasions; 1268 Borders teams played at these grounds, with 344 injury episodes being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 11 publications
1
29
1
Order By: Relevance
“…However, previous studies in New Zealand and Ireland reported that over half of all injuries in rugby union occurred on softer sports grounds 38 39. Conversely, a more recent and detailed epidemiological study demonstrated an increased injury incidence on harder grounds,2 although this study only classified ground hardness qualitatively.…”
Section: Discussionmentioning
confidence: 89%
“…However, previous studies in New Zealand and Ireland reported that over half of all injuries in rugby union occurred on softer sports grounds 38 39. Conversely, a more recent and detailed epidemiological study demonstrated an increased injury incidence on harder grounds,2 although this study only classified ground hardness qualitatively.…”
Section: Discussionmentioning
confidence: 89%
“…Another example of logistic regression can be found in Lee and Garraway (2000), who identi® ed the in¯uence of environmental factors on rugby union injuries. Using team possessions as the units of observation, Pollard and Reep (1997) recognized that adopting `goals scored' as their categorical [0,1] dependent variable would result in too few`g oals scored' compared with the many team possessions that failed to result in a goal.…”
Section: Discussionmentioning
confidence: 99%
“…While many putative risk factors are named in the literature, there have been few attempts to confirm these in analytical studies, with two notable exceptions undertaken in Scotland47 and New Zealand 810. The objective of this study was to investigate the independent effect on injury incidence of a number of commonly postulated risk factors (as listed in methods) 59 11…”
Section: Introductionmentioning
confidence: 99%